SAT0632 Ultrasound in the management of rheumatoid arthritis using a novel pragmatic algorithm: a multicentric observational study. (12th June 2018) - Bonfiglioli, K.R.; Chakr, R.; Lima, R.; Paiva, E.; Moss, I.; Giorgi, R.; Rassi, M.; Cardoso, R.; Nadaf, F.; Santos, R.; Ribeiro, D.; Arruda, L.; et al.
Abstract : Background: Recently, novel algorithms for the pragmatic use of US in the management of RA patients were published in order to guide US use in various clinical scenarios. Objectives: To evaluate the performance of the 2016 algorithm 1 proposed for evaluation of therapeutic response and its potential to contribute in decision-making. Methods: Multicentric (5 centres), cross-sectional and observational study. Inclusion criteria: Patients older than 18 years old, RA diagnosis (ACR/EULAR criteria), receiving stable doses of conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) for the last six months. Exclusion criteria: use of biological DMARDs, severe articular deformities. Patients were submitted to clinical examination, CDAI(Clinical Disease Activity Index) was recorded and US examination performed by trained rheumatologists blinded to CDAI results. The following joints were examined: wrists, metacarpophalangeal (2 and 3), proximal interphalangeal (2 and 3) and metatarsophalangeal (2 and 5), in addition to any symptomatic joint.Synovitis was determined according to OMERACT.Joint distension (grey scale, GS) and Power Doppler (PD) graded on semiquantitative scale: absent=0, mild=1, moderate=2, intense=3. Total individual GS and PD scores were calculated by the sum of each joint scores.Therefore, each participant had two separate scores (GS and PD). Results: 139 patients were included: 93% women, RF positive in 66%, age=57±11 [mean ±SD]yr, disease duration=10±8 year. Almost half (47.5%, n=66) of the patients had moderate/high disease activity, CDAI=20.65±10.66[mean ±SD]; while 52.5%(n=73) were in low activity/remission, CDAI=4.43±3.24.US: ofthe 66 patients with moderate/high disease activity, 26 patients (39.3%) presented negative PD and lowGS score: 5.11±2.67[mean ±SD] vs. 40 patients with positive PD(PD=4.93±4.9)and a higher GS score (11.6±6.29, p<0.0001). CDAI in positive and negative PD subgroups was similar: mean (SD) values 21.81±11.32 vs. 18.86±9.02, p=0.13.Regarding CDAI low activity/remission group, 74% had negative PD, GS=4.5±3, 6 and 5 (6.85%) were in US remission. Of these 5 patients, only one was in CDAI remission. From 26 patients in clinical remission, 4 (15.4%) patients had positive PD and GS score greater than 5, one was in US remission and the remaining (80.8%)presented negative PD but mild GS score. Conclusions: Our study confirms that patients in CDAI remission may present active synovitis upon US exam. Likewise, patients with US remission may present falsely elevated clinical metrics possible due to the influence of other non-inflammatory comorbidities. Similarly in patients with moderate/high disease activity, US can alert to the possibility of other factors adding to high clinical scores. The US contributedto differentiate both clinical scenarios, with potential to optimise the therapeutic approach. Reference: [1] D'Agostino MA, et al. Ann Rheum Dis2016;0:1–7. Disclosure of Interest: None declared